Perilous power : the Middle East & U.S. foreign policy : dialogues on terror, democracy, war, and justice - Chomsky, Noam, 1928-; Achcar, Gilbert, 1951- (Boulder [etc.] : Paradigm, 2007)
From Publishers Weekly This intriguing series of conversations between like-minded peers about America in the Middle East pairs dissident intellectual Chomsky with Achcar, who is less well known for critiques of U.S. foreign policy (Clash of Barbarisms). Drawing on deep historical background, they deconstruct Western assumptions about international politics: "Every state you can think of is based on violence, repression... the state system itself has no inherent legitimacy." While refreshingly careful to note when their conclusions aren't backed by rigorous documentation, both make broad assumptions about human behavior, while easily disregarding contradictions. For example they rely on opinion polls to indicate the desires of a given people (as opposed to the ruling elite), but reject the once-broad Palestinian support of the Oslo Peace Accords, for instance, because, as Chomsky says, the Palestinians "were just totally deluded." Similarly, they give little weight to nonrational influences-religiosity
Fear-where these almost certainly played a key role in forming public opinion, such as in Arab disillusionment with secular nationalism or Israeli presumptions of anti-Semitism. Particularly in Chomsky's case, this can extend to an unfortunate contempt for those with whom he disagrees. Both men raise vital questions, but some readers may be alienated by the authors' often dismissive manner. (Nov.) Copyright Â Reed Business Information, a division of Reed Elsevier Inc. All rights reserved. Product Description The volatile Middle East is the site of vast resources, profound passions, frequent crises, and long-standing conflicts, as well as a major source of international tensions and a key site of direct U.S. intervention. Two of the most astute analysts of this part of the world are Noam Chomsky, the preeminent critic of U.S. foreign policy, and Gilbert Achcar, a leading specialist of the Middle East who lived in that region for many years. In their new book, Chomsky and Achcar bring a keen understanding
Of the internal dynamics of the Middle East and of the role of the United States, taking up all the key questions of interest to concerned citizens, including such topics as terrorism, fundamentalism, conspiracies, oil, democracy, self-determination, anti-Semitism, and anti-Arab racism, as well as the war in Afghanistan, the invasion and occupation of Iraq, the Israeli-Palestinian conflict, and the sources of U.S. foreign policy. This book provides the best readable introduction for all who wish to understand the complex issues related to the Middle East from a perspective dedicated to peace and justice.
Keywords: Midden-Oosten.; Oorlogsethiek; Verenigde Staten -- Buitenlandse politiek